Tema dan Amanat dalam Novel Layangan Putus Karya Mommy ASF - Denastri Matara; Richard Oematan; Sanhedri Boimau (JURNAL ILMIAH NUSANTARA, 2026)
The problem discussed in this study is the main theme and the message contained in the novel Layangan Putus by Mommy ASF. The purpose of this study is to identify the theme and the message or moral lesson in the novel Layangan Putus by Mommy ASF. The benefit of this study is to contribute to the development of Indonesian literary studies, particularly the analysis of intrinsic elements of theme and message, and to serve as a reference for readers, educators, and subsequent researchers in understanding the moral, social, and psychological values found in contemporary literary works. The theory used is structural theory. The research method employed is descriptive qualitative with a structural approach. The research data consist of words, phrases, sentences, and paragraphs that contain themes and messages, while the data source is the novel Layangan Putus published in 2020. Data collection techniques were carried out through close reading and recording relevant quotations, which were then analyzed through the steps of data examination, identification, analysis based on structural theory, and drawing conclusions. The results show that the main theme of the novel Layangan Putus is the breakdown of a household due to betrayal (polygamy), which leads to a loss of trust. This theme is supported by subsidiary themes such as communication crisis and emotional neglect, struggle and resilience of women, the impact of conflict on children, religiosity or hijrah (spiritual transformation), and the influence of social media. The message contained in this novel emphasizes the importance of communication and openness in a household, keeping commitments, self-respect, prioritizing the child's interests, practicing religious values with empathy and justice, as well as being wise in using social media and not being quick to judge.